Road to Plato: Gadamer’s first steps in Marburg (1919-1928) - Bey, Facundo (Anales del Seminario de Historia de la Filosofía, 2020)
This article aims to readdress Hans-Georg Gadamer’s first encounter with Plato’s philosophy through his earlier academic journey, the direct and indirect influence exerted by his celebrated mentors at the University of Marburg, and his early publications. For this, I will resort not only to his intellectual biography, but also to neglected texts of Gadamer, such as his 1922 doctoral thesis, reviews and articles published between 1924 and 1928, correspondence, both edited and unpublished, philosophical interviews, as well as archive footage. I will seek to determine the role of his early mentors around Plato’s interpretation through the analysis of the evolution of Gadamer’s theoretical positions in order to elucidate his critical reassessments. In the conclusions, I will make an attempt to deepen on Gadamer’s process of reception, rupture and emancipation around the then-dominant interpretations of Marburg neo-Kantianism, especially on the link between the philosophy of Plato and Aristotle, as well as the transformative character of Gadamer’s approach to the phenomenology of Scheler and Heidegger, and his incursion into classical philology.